Probing H2 autoionizing states with femto and attosecond laser pulses. (2009)
ABSTRACT: We show the relevance that molecular autoionizing states display in some recent experiments related to the symmetry-breaking in molecular-frame photoelectron angular distributions in H2 when exposed to intense xuv femtosecond laser pulses, and others related to the electron (proton) localization when subject to attosecond pump-probe laser schemes. Our theoretical method solves the time-dependent Schr¨odinger equation with an spectral method that expands the wave function in terms of H2 correlated stationary vibronic states including all electronic and vibrational degrees of motion. Time-resolved asymmetric electron angular distributions are obtained at specific proton kinetic energies due to the delayed autoionization from H2 doubly excited states, which induces interferences between gerade (1s(sigma)g) and ungerade (2p(sigma)u) ionization channels. We also study photoionization of H2 exposed to a xuv attosecond pump pulse plus a time-delayed IR femtosecond probe pulse. Fast alternating asymmetries in the proton ejection (electron localization) are obtained as a function of the time delay between the pump and the probe pulses. Finally, we deal with the process of (xuv) two-photon double ionization of H2 under the assumption of having both sequential and non-sequential absorption processes.